Inverse coefficient problem fоr a two-dimensional parabolic equation in a domain with free boundary - Snitko, H. A.; Снітко, Г. А. (Institute of Mathematics, NAS of Ukraine, 2016)
We establish the conditions of unique solvability of the inverse problem of finding the minor coefficient in a two-dimensional parabolic equation in the domain for which the location of a part of its boundary is described by a function in the form of a product of an unknown function of time and a given function of the space variable.